2013
DOI: 10.1155/2013/832857
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Empiric Antibiotic Usage in a Secondary Care Hospital, Karachi, Pakistan

Abstract: Objectives. (1) To determine the indications, frequency, and types of antibiotics used in hospitalized paediatric patients at tertiary care hospital and (2) to evaluate whether the prescribed antibiotics were based on the isolation of organism and their sensitivity. Study Design. Descriptive observational hospital based study. Results. A total of 131 patients were included over 6 months of study period, in whom antibiotics were prescribed at the time of admission. The majority were between 1 and 5 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Although various international guidelines recommend the limited use of antibiotics in ARTIs, the noncompliance of these guidelines and the frequency of prescribing antibiotics in these infections is common in the healthcare system of Pakistan [ 9 , 10 ]. Evidence suggests that the unwanted use of antibiotics (e.g., cephalosporins) in pneumonia and bronchitis has economically burdened the healthcare system by causing a significant increase in the incidence of antimicrobial resistance, prescribing errors, and patients’ length of stay (LOS) in hospital [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although various international guidelines recommend the limited use of antibiotics in ARTIs, the noncompliance of these guidelines and the frequency of prescribing antibiotics in these infections is common in the healthcare system of Pakistan [ 9 , 10 ]. Evidence suggests that the unwanted use of antibiotics (e.g., cephalosporins) in pneumonia and bronchitis has economically burdened the healthcare system by causing a significant increase in the incidence of antimicrobial resistance, prescribing errors, and patients’ length of stay (LOS) in hospital [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the use of ceftriaxone in this hospital is selective as findings from other studies identified ceftriaxone as the most common antibiotic prescribed in their hospitals. [14,17,19,20] Ampicillin/cloxacillin combination was also observed to be the second most commonly prescribed antibiotic in the hospital. This fixed dose combination (FDC) was also reportedly used in Nepal [21] and Indian [22] hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[26] In Pakistan, findings from a study of 131 hospitalised children reported that blood cultures were done for 114 (87%) although only 10 cases (8.8%) were found to be culture positive. [14] Palikhe [21] reported that among 121 patients clinically diagnosed with infectious diseases, specimens were taken for cultures in only 24 cases (19.8%), out of which 13 specimens (54.2%) showed positive culture results. Another study reported that doctors in two healthcare facilities did not routinely send samples for microbiological testing, implying that there was no laboratory confirmation performed to adjust the initial empiric antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Pakistan, Nizami et al in a community-based study and Ali et al in a hospital-based study reported 39% and 86.2% of irrational antimicrobial prescription respectively. 5,6 Osam-Tewiah reported 73% of irrational antimicrobial prescription in Ghana while Howteerakul et al reported 72.6% in Thailand. 7,8 Since most diarrhea-related deaths occur in developing countries and care givers' of under-fives with acute watery diarrhea often visit public health facilities for treatment, it becomes necessary to periodically evaluate the extent of adherence of health workers to the current recommendations on the case management of acute watery diarrhea in these facilities.…”
Section: Introductionmentioning
confidence: 99%